Pengaruh Pengawasan, Insentif Dan Profesionalisme Kerja Terhadap Disiplin Kerja Tenaga Kesehatan Di Puskesmas Nanggalo Siteba Kota Padang - Nesa, Nesa; Lucy Chairoel (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the influence of supervision, incentives and work professionalism on work discipline of health workers at the Nanggalo Siteba Health Center, Padang City. This study uses a quantitative approach with a saturated/census sampling method of 60 health workers. Data analysis techniques in this study are research instrument testing, classical assumption testing, multiple linear regression analysis and hypothesis testing using the SPSS version 30 program. The results of hypothesis testing in this study indicate that 1) supervision partially has a positive and significant effect on work discipline, 2) incentives partially has a positive and significant effect on work discipline, 3) work professionalism has a positive and significant effect on work discipline, 4) supervision, incentives and work professionalism simultaneously have a positive and significant effect on work discipline.